2018
DOI: 10.1111/asj.13125
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interaction between leucine and acetate on the milk protein synthesis in bovine mammary epithelial cells

Abstract: The interaction between Leucine (Leu) and acetate affecting milk protein synthesis in the bovine mammary epithelial cells (BMECs), and underlying the molecular mechanisms are not well understood. The objectives of this study were to investigate the effect of Leu, acetate, and their interaction on the expression of genes involved in milk protein synthesis, and JACK2/STAT5, mTOR and AMP-activated protein kinase (AMPK) signaling pathway. The study was a 2 × 6 factorial arrangement with treatments: Leu concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…This is consistent with our finding that GLUT1 exression was increased in 100%DIF compared to 99%DIF. Zhao et al (2019) reported an increase of cellular ATP concents by the supplementation of Ace. Ace was not affected by the GLUT1 levels in this study; however, it may be a potential energy source in mammary epithelial levels.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This is consistent with our finding that GLUT1 exression was increased in 100%DIF compared to 99%DIF. Zhao et al (2019) reported an increase of cellular ATP concents by the supplementation of Ace. Ace was not affected by the GLUT1 levels in this study; however, it may be a potential energy source in mammary epithelial levels.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, 0.15 mM His was selected for the verification of its combination effect with Ace. The supplementation of Ace presented an increase of the β-casein mRNA level in pbMECs cultured with DMEM/F12 [ 13 ]. This is consistent with our results when 0.15–0.6 mM Ace was supplemented to the MAC-T cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations